MODEL PENERIMAAN TEKNOLOGI MAHASISWA CALON GURU TERHADAP BERBAGAI APLIKASI SELAMA PEMBELAJARAN DALAM JARINGAN DAN KESIAPAN MEREKA MENJADI PENDIDIK BAGI GENERASI Z DAN ALPHA - Pipi Deswita; Adelia Alfama Zamista (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2021)
Becoming a professional teacher requires qualified teaching skills. To hone their teaching skills, students are required to take micro teaching courses. During the pandemic, micro teaching courses were carried out online, therefore the course lecturers used various applications for the smooth running of lectures. This study is a descriptive study that aims to analyze student acceptance of the use of various applications in microteaching learning with the TAM approach and then see their readiness as prospective educators for generation z and generation alpha which are known as the very technology literate generation. The study was conducted on 66 students who took microteaching courses even semester 2020/2021. Based on the slovin formula, the samples taken were 57 people. From the results of research data processing, it was found that the average value of the seven successive variables was as follows, 3.21 for distance learning self-efficacy(SE), 2.65 for lack of time (LT), 3.19 for complexity (C ), 3.07 for perceived usefulness (PU), 2.9 for perceived ease of use (PEOU), 6) 3.17 for behavioral intention to use (BIU), and 3.08 for actual technology use (ATU). The results of the analysis show that distance learning self-efficacy is in the high category (indicated by 51 students in the high category, 5 quite low, and 1 low)